Preparation method of building thermal insulation material based on modified aerogel
Through the combination of modified aerogel and a variety of functional materials, multifunctional building insulation materials are formed, which solves the problems of poor insulation effect, flammability and poor environmental protection in high temperature environments, and achieves high efficiency Insulation, versatility and environmental protection.
Patent Information
- Application Number
- CN202411332135.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-31
AI Technical Summary
Traditional building insulation materials have poor thermal insulation effect in high temperature environments, are flammable and have poor environmental protection, and lack versatility.
Using modified aerogel-based building insulation materials, combining photonic crystals, carbon nanotubes, phase change energy storage microspheres, photothermal conversion nanoparticles, bio-based polymers, nanocellulose, reflective pigments and infrared reflectors , multifunctional thermal insulation material is formed through multi-stage pore structure and self-assembly technology.
Significantly improve the thermal insulation performance, realize light-heat conversion and intelligent temperature regulation, improve environmental protection and sustainability, and have versatility and high mechanical properties.
Smart Images

Figure CN119219394A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building thermal insulation materials, and in particular to a method for preparing a building thermal insulation material based on modified aerogel. Background Art
[0002] With the continuous increase in global energy demand and the growing awareness of environmental protection, building energy conservation has become an important research field. As a key component of energy-saving technology, the improvement of the performance of building insulation materials is of great significance for reducing energy consumption and greenhouse gas emissions. Although traditional building insulation materials, such as polystyrene and polyurethane, can play a role in insulation to a certain extent, their insulation effect is limited in high temperature environments, and they often have problems such as flammability and poor environmental protection.
[0003] The deficiencies in the prior art are mainly reflected in the following aspects:
[0004] Limited insulation performance: The insulation effect of traditional insulation materials will be significantly reduced under high temperature or long-term use, and cannot meet the building insulation needs under extreme climatic conditions.
[0005] Poor environmental friendliness: Some traditional insulation materials release harmful substances during production and use, causing environmental pollution, and are difficult to degrade after being discarded.
[0006] Safety issues: Some insulation materials are flammable, pose a fire safety hazard, and may produce toxic gases when burned.
[0007] Single function: Traditional insulation materials often only have a single insulation function and lack multifunctional integration, such as photothermal conversion and phase change energy storage.
[0008] Therefore, we proposed a method for preparing building thermal insulation materials based on modified aerogels to solve the above problems. Summary of the invention
[0009] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a method for preparing a building thermal insulation material based on modified aerogel.
[0010] In order to achieve the above object, the present invention adopts the following technical solutions:
[0011] The building thermal insulation material based on modified aerogel comprises the following components in parts by weight: 30-50 parts of modified aerogel, 5-15 parts of photonic crystals, 2-8 parts of carbon nanotubes, 10-20 parts of phase change energy storage microspheres, 1-5 parts of photothermal conversion nanoparticles, 10-30 parts of bio-based polymers, 5-15 parts of nanocellulose, 1-5 parts of reflective pigments, 5-15 parts of glass microspheres, and 1-5 parts of infrared reflective agents.
[0012] As the preferred technical solution:
[0013] The modified aerogel-based building insulation material as described above includes the following components in parts by weight: 40 parts of modified aerogel, 9 parts of photonic crystals, 5 parts of carbon nanotubes, 14 parts of phase change energy storage microspheres, 3 parts of photothermal conversion nanoparticles, 18 parts of bio-based polymers, 10 parts of nanocellulose, 4 parts of reflective pigments, 8 parts of glass microspheres, and 3 parts of infrared reflectors.
[0014] The building thermal insulation material based on modified aerogel as described above, wherein the modified aerogel is silica aerogel, the photonic crystal is silica nanosphere, the carbon nanotube is multi-walled carbon nanotube, the phase change energy storage microsphere is one of organic phase change energy storage microsphere and inorganic phase change energy storage microsphere, the photothermal conversion nanoparticle is one of gold nanoparticle and black titanium dioxide nanoparticle, the bio-based polymer is one of polylactic acid and polyhydroxyalkanoate, the nanocellulose is one of cellulose nanocrystal and cellulose nanofiber, the reflective pigment is one of titanium dioxide and zinc oxide, the glass microsphere is one of hollow glass microsphere and high silica glass microsphere, and the infrared reflector is one of indium tin oxide nanoparticle and boron nitride nanosheet.
[0015] The building thermal insulation material based on modified aerogel as described above, wherein the average pore size of the modified aerogel is 2 to 50 nm, the bandgap width of the photonic crystal is 500 to 2000 nm, the length of the carbon nanotube is 5 to 50 μm, the particle size of the phase change energy storage microsphere is 1 to 10 μm, the particle size of the photothermal conversion nanoparticle is 5 to 50 nm, the glass transition temperature of the bio-based polymer is -20 to 50° C., the cellulose content of the nanocellulose is ≥98%, the particle size of the reflective pigment is 100 to 500 nm, the wall thickness of the glass microsphere is 50 to 500 nm, and the infrared reflectivity wavelength range of the infrared reflector is 8 to 14 μm
[0016] In the building thermal insulation material based on modified aerogel as described above, the bio-based polymer forms a three-dimensional network structure through chemical or physical cross-linking, the modified aerogel has a multi-level pore structure, wherein the multi-level pore structure is tightly combined with the bio-based polymer matrix, and the photonic crystal is embedded in the porous structure of the modified aerogel by a self-assembly method to form an optical performance layer, and the thermal insulation performance index is set to TP.
[0017] but
[0018] Where d0, d1, d2, d3, ..., dn are coefficients, CD represents the degree of crosslinking, PSD represents the pore structure parameter, and EC represents the degree of photonic crystal embedding. is a summation term.
[0019] Phase change energy storage microspheres are composed of a core-shell structure, the core is a phase change material, and the shell is a material with enhanced thermal conductivity and stability.
[0020] The second aspect of the present invention provides a method for preparing a building thermal insulation material based on modified aerogel, comprising the following steps:
[0021] S1: Select tetraethyl orthosilicate as the silicon source, prepare hydrophobic and heat-resistant organosilanes as modifiers, perform surface treatment on carbon nanotubes, prepare nanocellulose using enzymatic hydrolysis, prepare photonic crystal materials and reflective pigments, select appropriate phase change energy storage microspheres, photothermal conversion nanoparticles, bio-based polymers, glass microspheres and infrared reflectors, and ensure their quality is pure and free of impurities;
[0022] S2: dissolving tetraethyl orthosilicate in ethanol to form a uniform solution, slowly adding the catalyst solution under stirring conditions to promote the hydrolysis and polycondensation reaction of the silicon source, introducing ultrasonic treatment to promote the homogenization of the sol system, uniformly dispersing the phase change energy storage microspheres and photothermal conversion nanoparticles in the sol system, adding methyltriethoxysilane, and introducing it into the aerogel network by chemical grafting;
[0023] S3: The sol is allowed to stand and gelled under the condition of gradient temperature increase, the gelling rate is controlled, the gel is placed in an autoclave, supercritical carbon dioxide is introduced, the temperature and pressure are precisely controlled, the solvent is rapidly discharged from the gel under the supercritical state, and after drying, a modified aerogel block is obtained;
[0024] S4: Dispersing nanocellulose powder in water, adding a dispersant, and homogenizing the dispersion using a high-pressure homogenizer to obtain a finer fiber size and a more uniform dispersion effect, dissolving the bio-based polymer in an appropriate solvent, and mixing it evenly with the nanocellulose dispersion, using a vacuum-assisted impregnation method to evenly impregnate the mixed dispersion of nanocellulose and bio-based polymer into the aerogel block, and removing excess liquid by vacuum filtration to achieve a close composite of nanocellulose, bio-based polymer and aerogel matrix;
[0025] S5: Prepare the photonic crystal film by self-assembly method, mix the reflective pigment with the solvent to form a uniform pigment slurry, add glass beads and infrared reflective agent to the pigment slurry and mix them evenly, mix the pigment slurry with the photonic crystal film, add surfactant to improve the dispersion and stability of the pigment, and apply the coating on the surface of the composite thermal insulation material by combining spraying and scraping;
[0026] S6: Curing the coating to firmly adhere nanocellulose, photonic crystals, reflective pigments, glass beads, infrared reflectors, and bio-based polymers to the surface of the material
[0027] As the preferred technical solution:
[0028] According to the method for preparing a building thermal insulation material based on modified aerogel as described above, in S4, nanocellulose powder is dispersed in water to form a dispersion with a concentration of 5 to 10%, a dispersant is added, and its addition amount is controlled to be 1 to 3% of the mass of nanocellulose, and the dispersion is homogenized by a high-pressure homogenizer, the pressure is controlled at 20 to 40 MPa, and the treatment time is 30 to 50 minutes, the bio-based polymer is dissolved in water, and its concentration is controlled to be 5 to 15%, and the bio-based polymer is evenly mixed with the nanocellulose dispersion; a vacuum-assisted impregnation method is used to evenly impregnate the mixed dispersion of nanocellulose and bio-based polymer into the aerogel block, the vacuum degree is controlled at -0.08 to -0.1 MPa, and the impregnation time is 2 to 4 hours, and excess liquid is removed by vacuum filtration to achieve a tight composite of nanocellulose, bio-based polymer and aerogel matrix.
[0029] In the method for preparing a building thermal insulation material based on modified aerogel as described above, in S5, a self-assembly method is used to prepare a photonic crystal film, and the film thickness is controlled to be 50 to 200 nm. A reflective pigment is mixed with a solvent to form a uniform pigment slurry, and the pigment concentration is 10 to 30%. Glass beads and infrared reflectors are added to the pigment slurry, and the addition amount is controlled to be 5 to 15% of the pigment mass, and the mixture is mixed evenly. The pigment slurry is mixed with the photonic crystal film, and sodium dodecyl sulfate is added, and the addition amount is controlled to be 1 to 5% of the pigment mass to improve the dispersion and stability of the pigment. A coating is applied on the surface of the composite thermal insulation material by a combination of spraying and scraping, and the coating thickness is controlled to be 10 to 50 μm.
[0030] The method for preparing a building thermal insulation material based on modified aerogel as described above, wherein the modified aerogel is copolymerized and modified by methyltriethoxysilane and ethyl orthosilicate to form a modified aerogel with a three-dimensional network structure, wherein the modified aerogel has a multi-level pore structure, wherein the pore structure includes micropores, mesopores and macropores, and glass microspheres are dispersed in the modified aerogel.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] Significantly improve thermal insulation performance: The low thermal conductivity and excellent pore structure of the modified aerogel effectively prevent the transfer of heat, making the material have excellent thermal insulation effect.
[0033] Multifunctional integration: Photonic crystals and reflective pigments can reflect sunlight and reduce the absorption of solar radiation heat; carbon nanotubes and photothermal conversion nanoparticles can convert part of the absorbed light energy into heat energy to achieve photothermal conversion; phase change energy storage microspheres can store and release heat energy to achieve intelligent control of the temperature inside the building. The integration of these functions makes the material have multiple other functions while being heat-insulating.
[0034] Environmentally friendly and sustainable: The use of bio-based polymers and nanocellulose improves the environmental friendliness and sustainability of the material, which is in line with the concept of modern green buildings.
[0035] Multiple components synergistically increase thermal insulation performance: The modified aerogel itself has an extremely low thermal conductivity, while the photonic crystals and reflective pigments can reflect sunlight and reduce the absorption of solar radiation heat. The synergistic effect of these three can form an effective thermal barrier, significantly reduce the heat transfer of buildings, and improve thermal insulation performance. Bio-based polymers and nanocellulose have good mechanical properties and stability, which can enhance the overall performance of modified aerogel composites. This synergistic effect enables the material to maintain stable thermal insulation performance during long-term use and extend its service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a line graph of thermal conductivity data of the embodiments and comparative examples of the present invention;
[0037] Figure 2 It is a line graph of tensile strength data of the embodiments and comparative examples of the present invention. DETAILED DESCRIPTION
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. In the event of a conflict, the definitions in the specification shall prevail. "When mass, concentration, temperature, time, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood to specifically disclose all ranges formed by any pairing of any upper range limit or preferred value with any lower range limit or preferred value, regardless of whether the range is disclosed separately. For example, a range of 1-50 should be understood to include 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91 6, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50, any number, combination of numbers, or subrange, and all decimal values between the above integers, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, and 1.9. With respect to subranges, "nested subranges" extending from any endpoint within the range are specifically contemplated. For example, nested subranges of the exemplary range 1-50 may include 1-10, 1-20, 1-30, and 1-40 in one direction, or 50-40, 50-30, 50-20, and 50-10 in the other direction."
[0039] The present invention is further explained below in conjunction with specific examples. The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0040] The building thermal insulation material based on modified aerogel comprises the following components in parts by weight: 30-50 parts of modified aerogel, 5-15 parts of photonic crystals, 2-8 parts of carbon nanotubes, 10-20 parts of phase change energy storage microspheres, 1-5 parts of photothermal conversion nanoparticles, 10-30 parts of bio-based polymers, 5-15 parts of nanocellulose, 1-5 parts of reflective pigments, 5-15 parts of glass microspheres, and 1-5 parts of infrared reflectors.
[0041] Among them, the modified aerogel is silica aerogel, the photonic crystal is silica nanosphere, the carbon nanotube is multi-walled carbon nanotube, the phase change energy storage microsphere is one of organic phase change energy storage microsphere and inorganic phase change energy storage microsphere, the photothermal conversion nanoparticle is one of gold nanoparticle and black titanium dioxide nanoparticle, the bio-based polymer is one of polylactic acid and polyhydroxyalkanoate, the nanocellulose is one of cellulose nanocrystal and cellulose nanofiber, the reflective pigment is one of titanium dioxide and zinc oxide, the glass microbeads are one of hollow glass microbeads and high silica glass microbeads, and the infrared reflector is one of indium tin oxide nanoparticles and boron nitride nanosheets.
[0042] The average pore size of the modified aerogel is 2 to 50 nm, the bandgap width of the photonic crystal is 500 to 2000 nm, the length of the carbon nanotube is 5 to 50 μm, the particle size of the phase change energy storage microspheres is 1 to 10 μm, the particle size of the photothermal conversion nanoparticles is 5 to 50 nm, the glass transition temperature of the bio-based polymer is -20 to 50° C., the cellulose content of the nanocellulose is ≥98%, the particle size of the reflective pigment is 100 to 500 nm, the wall thickness of the glass microbeads is 50 to 500 nm, and the infrared reflectivity wavelength range of the infrared reflector is 8 to 14 μm.
[0043] The bio-based polymer forms a three-dimensional network structure through chemical or physical cross-linking. The modified aerogel has a multi-level porous structure, in which the multi-level porous structure is closely combined with the bio-based polymer matrix. The photonic crystal is embedded in the porous structure of the modified aerogel by self-assembly to form an optical performance layer. The thermal insulation performance index is set as TP.
[0044] but
[0045] Where d0, d1, d2, d3, ..., dn are coefficients, CD represents the degree of crosslinking, PSD represents the pore structure parameter, and EC represents the degree of photonic crystal embedding. is a summation term.
[0046] Phase change energy storage microspheres are composed of a core-shell structure, the core is a phase change material, and the shell is a material with enhanced thermal conductivity and stability.
[0047] Three-dimensional network structure formation of bio-based polymers:
[0048] We use chemical or physical cross-linking methods to form cross-linking points between bio-based polymer molecular chains, thereby constructing a stable three-dimensional network structure. This structure not only enhances the mechanical properties of the material, but also provides a stable matrix for the embedding of other components.
[0049] Modified aerogels with hierarchical pore structures combined with bio-based polymers:
[0050] The modified aerogel has a unique multi-level pore structure, including macropores, mesopores and micropores. Through specific process conditions, these multi-level pore structures are closely combined with the bio-based polymer matrix to form a composite structure. This combination not only retains the low thermal conductivity of the modified aerogel, but also improves the overall stability and durability of the material.
[0051] Self-assembly of photonic crystals for embedding:
[0052] We use a self-assembly method to precisely embed photonic crystals into the porous structure of the modified aerogel to form an optical performance layer with excellent optical properties. This embedding method ensures that the photonic crystals can fully exert their functions of reflecting sunlight and reducing the absorption of solar radiation heat.
[0053] Setting and calculation of thermal insulation performance index TP:
[0054] In order to comprehensively evaluate the thermal insulation performance of building insulation materials, we set the thermal insulation performance index TP and use the following formula for calculation:
[0055]
[0056] Among them, d0, d1, d2, d3, …, dn are coefficients, which represent the degree of influence of different factors on thermal insulation performance. CD represents the degree of crosslinking, that is, the degree of crosslinking of the three-dimensional network structure of bio-based polymers; PSD represents the pore structure parameter, which describes the characteristics of the multi-level porous structure of the modified aerogel; EC represents the degree of photonic crystal embedding, which reflects the embedding of photonic crystals in the porous structure of the modified aerogel; Xi represents other factors that may affect thermal insulation performance, such as material thickness, density, etc.
[0057] We have obtained the following coefficients and variable values through experiments or literature data:
[0058] d0=1.0(basic thermal insulation performance)
[0059] d1=0.5 (coefficient of influence of cross-linking degree on thermal insulation performance)
[0060] d2=0.3 (the influence coefficient of pore structure parameters on thermal insulation performance)
[0061] d3=0.2 (the influence coefficient of the degree of photonic crystal embedding on thermal insulation performance)
[0062] CD = 0.8 (actual crosslinking degree)
[0063] PSD = 0.6 (actual pore structure parameter)
[0064] EC = 0.7 (actual photonic crystal embedding degree)
[0065] To simplify the calculation, we assume that only these three main factors affect the thermal insulation performance, that is, n=3, and there are no other additional X_i factors.
[0066] We can substitute the known values into the formula to calculate: TP = 1.72
[0067] Therefore, in this specific example, the thermal insulation performance index (TP) is calculated to be 1.72. The thermal insulation performance index of 1.72 is a relatively good value. The larger the thermal insulation performance index, the better the thermal insulation capacity of the material. This value can be used as a reference to evaluate and optimize the thermal insulation performance of building insulation materials. We can get good thermal insulation performance through calculation.
[0068] Through the above specific implementation methods, we have successfully prepared building thermal insulation materials based on modified aerogels and achieved excellent thermal insulation performance and versatility. At the same time, by setting and calculating the thermal insulation performance index TP, we can more accurately evaluate and optimize the thermal insulation performance of materials and provide new solutions for the field of building energy conservation.
[0069] Embodiment 1
[0070] The building thermal insulation material based on modified aerogel includes the following components in parts by weight: 30 parts of modified aerogel, 5 parts of photonic crystals, 2 parts of carbon nanotubes, 10 parts of phase change energy storage microspheres, 1 part of photothermal conversion nanoparticles, 10 parts of bio-based polymers, 5 parts of nanocellulose, 1 part of reflective pigments, 5 parts of glass microspheres, and 1 part of infrared reflector.
[0071] Among them, the modified aerogel is silica aerogel (Hebei Shuhao Energy Saving Technology Co., Ltd.), the photonic crystal is silica nanosphere (Nanoshell Co., Ltd. of the United States), the carbon nanotube is multi-walled carbon nanotube (Shenzhen Nanoport Co., Ltd.), the phase change energy storage microsphere is organic phase change energy storage microsphere (Shanghai Yuyu New Material Technology Co., Ltd.), the photothermal conversion nanoparticles are gold nanoparticles (Nanjing Jike Biotechnology Co., Ltd.), the bio-based polymer is polylactic acid (Kingfa Technology Co., Ltd.), the nanocellulose is cellulose nanocrystals (Shandong Longli Biotechnology Co., Ltd.), the reflective pigment is titanium dioxide (DuPont Titanium Dioxide (Shanghai) Co., Ltd.), the glass microbeads are hollow glass microbeads (Henan Hongtai Glass Microbeads Co., Ltd.), and the infrared reflector is indium tin oxide nanoparticles (Zhongke Leiming (Beijing) Technology Co., Ltd.).
[0072] The embodiment also provides a method for preparing a building thermal insulation material based on modified aerogel, which is characterized by comprising the following steps:
[0073] S1: Select tetraethyl orthosilicate (Wuhan Jiyesheng Chemical Co., Ltd.) as the silicon source, prepare hydrophobic and heat-resistant organosilanes as modifiers, perform surface treatment on carbon nanotubes, control the treatment temperature at 50°C, and the treatment time for 2 hours, use enzymatic hydrolysis to prepare nanocellulose, control the enzymatic hydrolysis temperature at 40°C, and the enzymatic hydrolysis time for 4 hours, prepare photonic crystal materials and reflective pigments, and control the pigment particle size within the range of 1μm, select 1μm phase change energy storage microspheres, 5nm photothermal conversion nanoparticles, 10nm bio-based polymers, 8μm glass microbeads, and 1μm infrared reflectors to ensure their quality is pure and free of impurities;
[0074] S2: dissolve tetraethyl orthosilicate in ethanol to form a uniform solution with a concentration of 10%, control the stirring speed at 500rpm, slowly add hydrochloric acid solution, control the dropping speed to 1 drop per second, introduce ultrasonic treatment with a frequency of 20kHz and a treatment time of 30 minutes, uniformly disperse phase change energy storage microspheres and photothermal conversion nanoparticles in the sol system, control their dispersion concentration to 5% of the total mass of the sol, and ensure uniform dispersion, add methyltriethoxysilane (Hubei Chengfeng Chemical Co., Ltd.), control its addition amount to 5% of the total mass of the sol, and introduce it into the aerogel network by chemical grafting;
[0075] S3: The sol was allowed to stand and gelled under the condition of gradient temperature increase. The temperature increase rate was controlled to be 5°C per hour and the gelation time was 12 hours. The gel was placed in an autoclave and supercritical carbon dioxide was introduced. The temperature was controlled to be 35°C and the pressure was 8MPa. This state was maintained for 2 hours to allow the solvent to be quickly discharged from the gel under the supercritical state. After drying, a modified aerogel block was obtained with a density of 0.05g / cm 3 ;
[0076] S4: Disperse the nanocellulose powder in water to form a dispersion with a concentration of 5%, add a dispersant, and control the added amount to be 1% of the mass of the nanocellulose. Use a high-pressure homogenizer to homogenize the dispersion, control the pressure at 20MPa, and process for 30 minutes. Dissolve the bio-based polymer in water, control the concentration to be 5%, and mix it evenly with the nanocellulose dispersion. Use a vacuum-assisted impregnation method to evenly impregnate the mixed dispersion of nanocellulose and bio-based polymer into the aerogel block, control the vacuum degree at -0.08MPa, and immerse for 2 hours. Remove excess liquid by vacuum filtration to achieve a close composite of nanocellulose, bio-based polymer and aerogel matrix.
[0077] S5: Prepare a photonic crystal film by a self-assembly method, control the film thickness to 50nm, mix the reflective pigment with the solvent to form a uniform pigment slurry, the pigment concentration is 10%, add glass beads and infrared reflective agent to the pigment slurry, control the addition amount to 5% of the pigment mass, and mix them evenly, mix the pigment slurry with the photonic crystal film, add sodium dodecyl sulfate, control the addition amount to 1% of the pigment mass, improve the pigment dispersion and stability, apply a coating on the surface of the composite thermal insulation material by a combination of spraying and scraping, and control the coating thickness to 10μm;
[0078] S6: Curing the coating, with the curing temperature controlled at 80°C and the curing time at 1 hour, so that the nanocellulose, photonic crystals, reflective pigments, glass beads, infrared reflective agents and bio-based polymers are firmly attached to the surface of the material.
[0079] Embodiment 2
[0080] The building thermal insulation material based on modified aerogel includes the following components in parts by weight: 50 parts of modified aerogel, 15 parts of photonic crystals, 8 parts of carbon nanotubes, 20 parts of phase change energy storage microspheres, 5 parts of photothermal conversion nanoparticles, 30 parts of bio-based polymers, 15 parts of nanocellulose, 5 parts of reflective pigments, 15 parts of glass microspheres, and 5 parts of infrared reflectors.
[0081] Among them, the modified aerogel is silica aerogel, the photonic crystal is silica nanosphere, the carbon nanotube is multi-walled carbon nanotube, the phase change energy storage microsphere is inorganic phase change energy storage microsphere (Shanghai Yuyu New Material Technology Co., Ltd.), the photothermal conversion nanoparticles are black titanium dioxide nanoparticles, the bio-based polymer is polyhydroxyalkanoate (Dongguan Shenghao Plastic Raw Materials Co., Ltd.), the nanocellulose is cellulose nanofiber (Zhejiang Jinjiahao Green Nanomaterials Co., Ltd.), the reflective pigment is zinc oxide (Shandong Lianke Technology Co., Ltd.), the glass microbeads are high silica glass microbeads (Henan Hongtai Glass Microbeads Co., Ltd.), and the infrared reflector is boron nitride nanosheets.
[0082] The embodiment also provides a method for preparing a building thermal insulation material based on modified aerogel, which is characterized by comprising the following steps:
[0083] S1: Select tetraethyl orthosilicate as the silicon source, prepare hydrophobic and heat-resistant organosilane as the modifier, perform surface treatment on carbon nanotubes, control the treatment temperature at 70°C, and the treatment time for 4 hours, use enzymatic hydrolysis to prepare nanocellulose, control the enzymatic hydrolysis temperature at 50°C, and the enzymatic hydrolysis time for 6 hours, prepare photonic crystal materials and reflective pigments, and control the pigment particle size within the range of 5μm, select 10μm phase change energy storage microspheres, 50nm photothermal conversion nanoparticles, 500nm bio-based polymers, 150μm glass microspheres, and 50μm infrared reflectors to ensure their quality is pure and free of impurities;
[0084] S2: dissolve tetraethyl orthosilicate in ethanol to form a uniform solution with a concentration of 20%, control the stirring speed at 1000rpm, slowly add hydrochloric acid solution, control the dropping speed to 2 drops per second, introduce ultrasonic treatment with a frequency of 40kHz and a treatment time of 50 minutes, uniformly disperse phase change energy storage microspheres and photothermal conversion nanoparticles in the sol system, control their dispersion concentration to 10% of the total mass of the sol, and ensure uniform dispersion, add methyltriethoxysilane, control its addition amount to 10% of the total mass of the sol, and introduce it into the aerogel network by chemical grafting;
[0085] S3: The sol was allowed to stand and gelled under the condition of gradient temperature increase. The temperature increase rate was controlled to be 10°C per hour and the gelation time was 14 hours. The gel was placed in an autoclave and supercritical carbon dioxide was introduced. The temperature was controlled to be 45°C and the pressure was 12MPa. This state was maintained for 4 hours to allow the solvent to be quickly discharged from the gel under the supercritical state. After drying, a modified aerogel block was obtained with a density of 0.2g / cm 3 ;
[0086] S4: Disperse the nanocellulose powder in water to form a dispersion with a concentration of 10%, add a dispersant, and control the added amount to be 3% of the mass of the nanocellulose. Use a high-pressure homogenizer to homogenize the dispersion, control the pressure at 40MPa, and process for 50 minutes. Dissolve the bio-based polymer in water, control the concentration to 15%, and mix it evenly with the nanocellulose dispersion. Use a vacuum-assisted impregnation method to evenly impregnate the mixed dispersion of nanocellulose and bio-based polymer into the aerogel block, control the vacuum degree at -0.1MPa, and immerse for 4 hours. Remove excess liquid by vacuum filtration to achieve a close composite of nanocellulose, bio-based polymer and aerogel matrix.
[0087] S5: Prepare photonic crystal film by self-assembly method, control the film thickness to 200nm, mix reflective pigment with solvent to form uniform pigment slurry, pigment concentration is 30%, add glass beads and infrared reflector to the pigment slurry, control the addition amount to 15% of the pigment mass, and mix them evenly, mix the pigment slurry with photonic crystal film, add sodium dodecyl sulfate, control the addition amount to 5% of the pigment mass, improve the pigment dispersion and stability, apply coating on the surface of composite thermal insulation material by combining spraying and scraping, control the coating thickness to 50μm;
[0088] S6: Curing the coating, with the curing temperature controlled at 120° C. and the curing time at 3 hours, so that the nanocellulose, photonic crystals, reflective pigments, glass beads, infrared reflective agents and bio-based polymers are firmly attached to the surface of the material.
[0089] Embodiment 3
[0090] The building thermal insulation material based on modified aerogel includes the following components in parts by weight: 35 parts of modified aerogel, 8 parts of photonic crystals, 4 parts of carbon nanotubes, 13 parts of phase change energy storage microspheres, 2 parts of photothermal conversion nanoparticles, 18 parts of bio-based polymers, 8 parts of nanocellulose, 2 parts of reflective pigments, 8 parts of glass microspheres, and 2 parts of infrared reflectors.
[0091] Among them, the modified aerogel is silica aerogel, the photonic crystal is silica nanosphere, the carbon nanotube is multi-walled carbon nanotube, the phase change energy storage microsphere is organic phase change energy storage microsphere, the photothermal conversion nanoparticles are gold nanoparticles, the bio-based polymer is polylactic acid, the nanocellulose is cellulose nanocrystals, the reflective pigment is titanium dioxide, the glass microbeads are hollow glass microbeads, and the infrared reflector is indium tin oxide nanoparticles.
[0092] The embodiment also provides a method for preparing a building thermal insulation material based on modified aerogel, which is characterized by comprising the following steps:
[0093] S1: Select tetraethyl orthosilicate as the silicon source, prepare hydrophobic and heat-resistant organosilane as the modifier, perform surface treatment on carbon nanotubes, control the treatment temperature at 55°C, and the treatment time is 2.5 hours. Prepare nanocellulose by enzymatic hydrolysis, control the enzymatic hydrolysis temperature at 42°C, and the enzymatic hydrolysis time is 4.5 hours. Prepare photonic crystal materials and reflective pigments, and control the pigment particle size within the range of 2μm. Select 4μm phase change energy storage microspheres, 20nm photothermal conversion nanoparticles, 200nm bio-based polymers, 50μm glass microspheres, and 10μm infrared reflectors to ensure their quality is pure and free of impurities;
[0094] S2: dissolve tetraethyl orthosilicate in ethanol to form a uniform solution with a concentration of 12%, control the stirring speed at 700rpm, slowly add hydrochloric acid solution, control the drop rate to 1 drop per second, introduce ultrasonic treatment with a frequency of 25kHz and a treatment time of 35 minutes, uniformly disperse phase change energy storage microspheres and photothermal conversion nanoparticles in the sol system, control their dispersion concentration to 6% of the total mass of the sol, and ensure uniform dispersion, add methyltriethoxysilane, control its addition amount to 6% of the total mass of the sol, and introduce it into the aerogel network by chemical grafting;
[0095] S3: The sol was allowed to stand and gelled under the condition of gradient temperature increase. The temperature increase rate was controlled to be 6°C per hour and the gelation time was 12 hours. The gel was placed in an autoclave and supercritical carbon dioxide was introduced. The temperature was controlled to be 38°C and the pressure was 9MPa. This state was maintained for 3 hours to allow the solvent to be quickly discharged from the gel under the supercritical state. After drying, a modified aerogel block was obtained and its density was controlled to be 0.1g / cm 3 ;
[0096] S4: Disperse the nanocellulose powder in water to form a dispersion with a concentration of 6%, add a dispersant, and control the added amount to be 2% of the mass of the nanocellulose. Use a high-pressure homogenizer to homogenize the dispersion, control the pressure at 25MPa, and process for 35 minutes. Dissolve the bio-based polymer in water, control the concentration to 8%, and mix it evenly with the nanocellulose dispersion. Use a vacuum-assisted impregnation method to evenly impregnate the mixed dispersion of nanocellulose and bio-based polymer into the aerogel block, control the vacuum degree at -0.09MPa, and immerse for 3 hours. Remove excess liquid by vacuum filtration to achieve a close composite of nanocellulose, bio-based polymer and aerogel matrix.
[0097] S5: Prepare photonic crystal film by self-assembly method, control the film thickness to 60nm, mix reflective pigment with solvent to form uniform pigment slurry, pigment concentration is 15%, add glass beads and infrared reflector to the pigment slurry, control the addition amount to 8% of the pigment mass, and mix them evenly, mix the pigment slurry with photonic crystal film, add sodium dodecyl sulfate, control the addition amount to 2% of the pigment mass, improve the pigment dispersion and stability, apply coating on the surface of composite thermal insulation material by combining spraying and scraping, control the coating thickness to 15μm;
[0098] S6: Curing the coating, with the curing temperature controlled at 90°C and the curing time at 2 hours, so that the nanocellulose, photonic crystals, reflective pigments, glass beads, infrared reflective agents and bio-based polymers are firmly attached to the surface of the material.
[0099] Embodiment 4
[0100] The building thermal insulation material based on modified aerogel includes the following components in parts by weight: 45 parts of modified aerogel, 13 parts of photonic crystals, 7 parts of carbon nanotubes, 18 parts of phase change energy storage microspheres, 4 parts of photothermal conversion nanoparticles, 25 parts of bio-based polymers, 12 parts of nanocellulose, 4 parts of reflective pigments, 12 parts of glass microspheres, and 4 parts of infrared reflectors.
[0101] Among them, the modified aerogel is silica aerogel, the photonic crystal is silica nanospheres, the carbon nanotubes are multi-walled carbon nanotubes, the phase change energy storage microspheres are inorganic phase change energy storage microspheres, the photothermal conversion nanoparticles are black titanium dioxide nanoparticles, the bio-based polymer is polyhydroxyalkanoate, the nanocellulose is cellulose nanofibers, the reflective pigment is zinc oxide, the glass microbeads are high-silica glass microbeads, and the infrared reflector is boron nitride nanosheets.
[0102] The embodiment also provides a method for preparing a building thermal insulation material based on modified aerogel, which is characterized by comprising the following steps:
[0103] S1: Select tetraethyl orthosilicate as the silicon source, prepare hydrophobic and heat-resistant organosilane as the modifier, perform surface treatment on carbon nanotubes, control the treatment temperature at 65°C, and the treatment time for 3 hours, use enzymatic hydrolysis to prepare nanocellulose, control the enzymatic hydrolysis temperature at 48°C, and the enzymatic hydrolysis time for 5 hours, prepare photonic crystal materials and reflective pigments, and control the pigment particle size within the range of 4μm, select 8μm phase change energy storage microspheres, 45nm photothermal conversion nanoparticles, 400nm bio-based polymers, 130μm glass microspheres, and 40μm infrared reflectors to ensure their quality is pure and free of impurities;
[0104] S2: dissolving tetraethyl orthosilicate in ethanol to form a uniform solution with a concentration of 18%, controlling the stirring speed at 900 rpm, slowly dripping hydrochloric acid solution, controlling the dripping speed to 2 drops per second, introducing ultrasonic treatment at a frequency of 35 kHz and a treatment time of 48 minutes, uniformly dispersing phase change energy storage microspheres and photothermal conversion nanoparticles in the sol system, controlling their dispersion concentration to 8% of the total mass of the sol, and ensuring uniform dispersion, adding methyltriethoxysilane, controlling its addition amount to 8% of the total mass of the sol, and introducing it into the aerogel network by chemical grafting;
[0105] S3: The sol was allowed to stand and gelled under the condition of gradient temperature increase. The temperature increase rate was controlled to be 8°C per hour and the gelation time was 13 hours. The gel was placed in an autoclave and supercritical carbon dioxide was introduced. The temperature was controlled to be 42°C and the pressure was 11MPa. This state was maintained for 3 hours to allow the solvent to be quickly discharged from the gel under the supercritical state. After drying, a modified aerogel block was obtained with a density of 0.18 g / cm 3 ;
[0106] S4: Disperse the nanocellulose powder in water to form a dispersion with a concentration of 9%, add a dispersant, and control the added amount to be 2% of the mass of the nanocellulose. Use a high-pressure homogenizer to homogenize the dispersion, control the pressure at 38MPa, and process for 48 minutes. Dissolve the bio-based polymer in water, control the concentration to be 13%, and mix it evenly with the nanocellulose dispersion. Use a vacuum-assisted impregnation method to evenly impregnate the mixed dispersion of nanocellulose and bio-based polymer into the aerogel block, control the vacuum degree at -0.09MPa, and immerse for 3 hours. Remove excess liquid by vacuum filtration to achieve a close composite of nanocellulose, bio-based polymer and aerogel matrix.
[0107] S5: Prepare photonic crystal film by self-assembly method, control the film thickness to 180nm, mix reflective pigment with solvent to form uniform pigment slurry, pigment concentration is 28%, add glass beads and infrared reflector to the pigment slurry, control the addition amount to 14% of the pigment mass, and mix them evenly, mix the pigment slurry with photonic crystal film, add sodium dodecyl sulfate, control the addition amount to 4% of the pigment mass, improve the pigment dispersion and stability, apply coating on the surface of composite thermal insulation material by combining spraying and scraping, control the coating thickness to 46μm;
[0108] S6: Curing the coating, with the curing temperature controlled at 112° C. and the curing time at 2 hours, so that the nanocellulose, photonic crystals, reflective pigments, glass beads, infrared reflective agents and bio-based polymers are firmly attached to the surface of the material.
[0109] Embodiment 5
[0110] On the basis of Example 4, the modified aerogel is copolymerized by methyltriethoxysilane and ethyl orthosilicate to form a modified aerogel with a three-dimensional network structure, wherein the modified aerogel has a multi-level pore structure, wherein the pore structure includes micropores, mesopores and macropores, and glass microbeads are dispersed in the modified aerogel.
[0111] Tetraethyl orthosilicate was used as the silicon source, and methyltriethoxysilane was introduced as a copolymer modifier.
[0112] In the sol-gel process, by controlling the reaction conditions (such as temperature, pH value, etc.), methyltriethoxysilane and ethyl orthosilicate are copolymerized to form a modified aerogel with a three-dimensional network structure.
[0113] The modified aerogel has a multi-level pore structure, including micropores, mesopores and macropores, which helps to improve the thermal insulation and adsorption capacity of the aerogel.
[0114] In Example 4, glass microspheres are mixed with other pigments and additives and then applied to the surface of the material.
[0115] In Example 5, the dispersion of glass microspheres in the modified aerogel is particularly emphasized. In the sol-gel process, the glass microspheres are evenly dispersed in the sol to form a composite material with the modified aerogel matrix. This dispersion method helps to further improve the overall performance and stability of the thermal insulation material.
[0116] The specific steps are as follows:
[0117] Following step S1 in Example 4, various components are prepared, and carbon nanotubes, nanocellulose, etc. are pretreated.
[0118] In step S2, in addition to ethyl orthosilicate, methyltriethoxysilane is also added for copolymerization modification. Other operations are the same as those in Example 4.
[0119] In step S3, the sol is allowed to stand and gel, at which point the glass microbeads are dispersed in the sol and form a composite material together with the modified aerogel.
[0120] Steps S4 to S6 are the same as those in Example 4, including the composite of nanocellulose and bio-based polymer, the preparation of photonic crystal film, and the final coating application and curing process.
[0121] Through the above steps, a modified aerogel building thermal insulation material with excellent thermal insulation performance can be prepared.
[0122] Comparative Example 1
[0123] The method for preparing building thermal insulation materials based on modified aerogel is basically the same as that of Example 4, except that the application of photonic crystals in the preparation method is removed.
[0124] Comparative Example 2
[0125] The method for preparing building thermal insulation materials based on modified aerogel is basically the same as that of Example 4, except that the application of phase change energy storage microspheres in the preparation method is removed.
[0126] Comparative Example 3
[0127] The method for preparing building thermal insulation materials based on modified aerogel is basically the same as that of Example 4, except that the application of bio-based polymer in the preparation method is eliminated.
[0128] Comparative Example 4
[0129] The method for preparing building thermal insulation materials based on modified aerogel is basically the same as that of Example 4, except that the application of carbon nanotubes and photothermal conversion nanoparticles in the preparation method is simultaneously eliminated.
[0130] The building thermal insulation materials based on modified aerogel prepared in the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 4 were tested, and the testing standards were as follows;
[0131] Thermal conductivity test standard
[0132] GB / T 10294-2008: The thermal conductivity of the specimen is calculated by measuring the heat flow caused by the temperature difference on both sides of the specimen under steady-state conditions, as well as the thickness and area of the specimen.
[0133] Combustion performance test standards
[0134] GB 8624-2012: Evaluates the combustion performance of materials by simulating fire conditions, including indicators such as flame propagation speed, heat release rate, and smoke generation.
[0135] Compression performance test standard
[0136] GB / T 8813: By applying pressure perpendicular to the surface of the specimen, the deformation and damage of the specimen during compression are measured to evaluate its compression performance.
[0137] Tensile strength test standard
[0138] GB / T 1040.1-2018: specifies the method for determining the tensile properties of plastics, including specimen preparation, test conditions, test steps and result calculation.
[0139] The results are shown in Table 1:
[0140] Table 1
[0141]
[0142] Through the above Table 1, it can be determined directly that in Examples 1 to 4, the thermal conductivity of Examples 1 to 4 is maintained at a low level, specifically between 0.014 and 0.015 W / (m·K). This shows that the materials of this group of examples have excellent thermal insulation properties, can effectively reduce the transfer of heat, and meet the basic requirements of building insulation materials. In terms of combustion performance, all embodiments have reached the A1 combustion performance level. From the perspective of compression rebound rate, the compression rebound rates of Examples 1 to 4 are between 94% and 95%. This means that this group of materials can quickly restore their original shape after being compressed, have good elastic recovery ability, and can maintain the stability and durability of the material. In terms of tensile strength, the tensile strength of all embodiments is between 240 and 248 kPa. This shows that this group of materials has high tensile properties, can withstand large tensile stresses without breaking, and ensure the structural integrity and stability of the material during use. In summary, Examples 1 to 4 all show the excellent performance of modified aerogel building insulation materials.
[0143] The thermal conductivity of Example 5 is 0.012W / (m·K), which is lower than 0.014W / (m·K) of Example 4. This means that Example 5 is more excellent in thermal insulation performance and can more effectively reduce heat transfer. Both have reached the A1 combustion performance grade, indicating that they both have extremely high fire resistance. The compression rebound rate of Example 5 is 95%, which is slightly improved compared to 94% of Example 4. This shows that Example 5 can restore its original shape more quickly after being compressed and has better elastic recovery ability. The tensile strength of Example 5 is 250kPa, which is an increase compared to 240kPa of Example 4. This means that Example 5 can withstand greater tensile stress without breaking and has higher structural integrity and stability. In summary, Example 5 further improves the thermal insulation performance, elastic recovery ability and tensile strength on the basis of Example 4.
[0144] The preparation method of the building thermal insulation material of comparative example 1 is basically the same as that of example 4, but the application of photonic crystals in the preparation method is removed. From the data, it can be seen that the thermal conductivity of comparative example 1 has increased compared with example 4, reaching 0.020W / (m·K), which indicates that the removal of photonic crystals may have a certain negative impact on the thermal insulation performance of the material. At the same time, the combustion performance level is also reduced to A2, indicating that the fire resistance has decreased. The compression rebound rate and tensile strength have also decreased, respectively, to 92% and 220kPa, indicating that the elasticity and tensile properties of the material have also been affected to a certain extent.
[0145] The preparation method of the building thermal insulation material of Comparative Example 2 is also basically the same as that of Example 4, but the application of phase change energy storage microspheres in the preparation method is removed. The data show that the thermal conductivity of Comparative Example 2 further increased to 0.022W / (m·K), and the thermal insulation performance continued to decline. The combustion performance level also remained at level A2, and the fire resistance was not restored. The compression rebound rate and tensile strength dropped to 93% and 200kPa respectively, and the elasticity and tensile properties of the material were further weakened. This shows that phase change energy storage microspheres make important contributions to the thermal insulation and mechanical properties of the material.
[0146] The preparation method of building thermal insulation materials in Comparative Example 3 is basically the same as that in Example 4, but the use of bio-based polymers in the preparation method is removed. From the data, the thermal conductivity of Comparative Example 3 has increased to 0.019W / (m·K). Although it is still lower than Comparative Examples 1 and 2, it still shows that the removal of bio-based polymers has a certain negative impact on the thermal insulation performance. The combustion performance level dropped to B1, and the fire resistance performance decreased significantly. The compression rebound rate and tensile strength also dropped to 90% and 180kPa respectively, which is the most obvious performance decline among all comparative examples. This shows that bio-based polymers play an important role in improving the fire resistance, thermal insulation and mechanical properties of materials.
[0147] The preparation method of the building thermal insulation material of Comparative Example 4 is basically the same as that of Example 4, but the use of carbon nanotubes and photothermal conversion nanoparticles in the preparation method is removed at the same time. The data show that the thermal conductivity of Comparative Example 4 has also increased to 0.021W / (m·K), and the thermal insulation performance is affected to a certain extent. The combustion performance level remains at level A2, indicating that even if these two nanomaterials are removed, the material still has certain fire resistance. The compression rebound rate is slightly reduced, but the tensile strength is reduced to 205kPa, indicating that the tensile properties of the material are affected to a certain extent. This shows that carbon nanotubes and photothermal conversion nanoparticles make important contributions to the thermal insulation and tensile properties of the material.
[0148] In summary, Example 4 retains all the key components of the modified aerogel building insulation material, including photonic crystals, phase change energy storage microspheres, bio-based polymers, etc. These components play their own unique roles in the material, and jointly improve the comprehensive performance of the material through synergistic effects. In contrast, the four comparative examples removed one or more of these key components, resulting in a decrease in the comprehensive performance of the material. Example 4 shows significant advantages and advantages in terms of thermal insulation performance, fire resistance, mechanical properties and comprehensive performance. These advantages make Example 4 have higher application value and market competitiveness in the field of building insulation materials.
[0149] The present invention achieves an extremely low thermal conductivity (such as 0.014W / (m·K) in the embodiment) by optimizing the components and preparation process, which is much lower than that of traditional thermal insulation materials. This is due to the synergistic effect of multiple components such as modified aerogel, photonic crystals, and carbon nanotubes, especially the high porosity and low thermal conductivity of the modified aerogel, and the spectrally selective reflection characteristics of the photonic crystals, which together improve the thermal insulation effect of the material.
[0150] The material of the present invention has achieved an A1 combustion performance rating, indicating that it has extremely high fire resistance. This is mainly due to the flame retardant effect of the bio-based polymer and other inorganic components, as well as the high thermal stability and non-flammability of the material as a whole. Through the composite reinforcement of nanocellulose and bio-based polymers, the material of the present invention exhibits excellent mechanical properties and stability. Nanocellulose provides additional mechanical support, while bio-based polymers enhance the flexibility and durability of the material.
[0151] The present invention uses environmentally friendly materials such as bio-based polymers, reduces dependence on fossil resources, and reduces carbon emissions during the production process. At the same time, the material itself can be recycled and reused, meeting the requirements of sustainable development.
[0152] Further optimization of Example 5 enables the material to maintain stable thermal insulation performance and other functional characteristics in more complex or extreme environments.
[0153] Bio-based polymers, reflective pigments, infrared reflectors and other components form multiple fire protection mechanisms in the material. Bio-based polymers themselves have good flame retardant properties, while reflective pigments and infrared reflectors can effectively reflect thermal radiation and reduce the temperature of the material surface, thereby improving the overall fire safety. The synergistic effect of the various components also improves the thermal and chemical stability of the material, allowing the material to maintain stable thermal insulation performance and structural integrity in high temperature environments. The synergistic effect between the various components achieves excellent thermal insulation performance, fire safety, mechanical properties and durability, environmental protection and sustainability, and a wide range of application adaptability.
[0154] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A building thermal insulation material based on modified aerogel, characterized in that: The invention comprises the following components in parts by weight: 30 to 50 parts of modified aerogel, 5 to 15 parts of photonic crystals, 2 to 8 parts of carbon nanotubes, 10 to 20 parts of phase change energy storage microspheres, 1 to 5 parts of photothermal conversion nanoparticles, 10 to 30 parts of bio-based polymers, 5 to 15 parts of nanocellulose, 1 to 5 parts of reflective pigments, 5 to 15 parts of glass microspheres and 1 to 5 parts of infrared reflectors.
2. The building thermal insulation material based on modified aerogel according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 40 parts of modified aerogel, 9 parts of photonic crystals, 5 parts of carbon nanotubes, 14 parts of phase change energy storage microspheres, 3 parts of photothermal conversion nanoparticles, 18 parts of bio-based polymers, 10 parts of nanocellulose, 4 parts of reflective pigments, 8 parts of glass microspheres and 3 parts of infrared reflectors.
3. The building thermal insulation material based on modified aerogel according to claim 1, characterized in that: The modified aerogel is a silica aerogel, the photonic crystal is a silica nanosphere, the carbon nanotube is a multi-walled carbon nanotube, the phase change energy storage microsphere is one of an organic phase change energy storage microsphere and an inorganic phase change energy storage microsphere, the photothermal conversion nanoparticle is one of a gold nanoparticle and a black titanium dioxide nanoparticle, the bio-based polymer is one of a polylactic acid and a polyhydroxyalkanoate, the nanocellulose is one of a cellulose nanocrystal and a cellulose nanofiber, the reflective pigment is one of a titanium dioxide and a zinc oxide, the glass microbeads are one of a hollow glass microbead and a high silica glass microbead, and the infrared reflector is one of an indium tin oxide nanoparticle and a boron nitride nanosheet.
4. The building thermal insulation material based on modified aerogel according to claim 1, characterized in that: The average pore size of the modified aerogel is 2 to 50 nm, the bandgap width of the photonic crystal is 500 to 2000 nm, the length of the carbon nanotube is 5 to 50 μm, the particle size of the phase change energy storage microsphere is 1 to 10 μm, the particle size of the photothermal conversion nanoparticle is 5 to 50 nm, the glass transition temperature of the bio-based polymer is -20 to 50° C., the cellulose content of the nanocellulose is ≥98%, the particle size of the reflective pigment is 100 to 500 nm, the wall thickness of the glass microsphere is 50 to 500 nm, and the infrared reflectivity wavelength range of the infrared reflector is 8 to 14 μm.
5. The building thermal insulation material based on modified aerogel according to claim 1, characterized in that: Bio-based polymers form a three-dimensional network structure through chemical or physical cross-linking. The modified aerogel has a multi-level porous structure, in which the multi-level porous structure is closely combined with the bio-based polymer matrix. Photonic crystals are embedded in the porous structure of the modified aerogel by self-assembly to form an optical performance layer. The thermal insulation performance index is set to TP, then: Where d0, d1, d2, d3, ..., dn are coefficients, CD represents the degree of crosslinking, PSD represents the pore structure parameter, and EC represents the degree of photonic crystal embedding. is a summation term; The phase change energy storage microspheres are composed of a core-shell structure, the core is a phase change material, and the shell is a material with enhanced thermal conductivity and stability.
6. A method for preparing a building thermal insulation material based on modified aerogel according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: Select tetraethyl orthosilicate as the silicon source, prepare hydrophobic and heat-resistant organosilanes as modifiers, perform surface treatment on carbon nanotubes, prepare nanocellulose using enzymatic hydrolysis, prepare photonic crystal materials and reflective pigments, select appropriate phase change energy storage microspheres, photothermal conversion nanoparticles, bio-based polymers, glass microspheres and infrared reflectors, and ensure their quality is pure and free of impurities; S2: dissolving tetraethyl orthosilicate in ethanol to form a uniform solution, slowly adding the catalyst solution under stirring conditions to promote the hydrolysis and polycondensation reaction of the silicon source, introducing ultrasonic treatment to promote the homogenization of the sol system, uniformly dispersing the phase change energy storage microspheres and photothermal conversion nanoparticles in the sol system, adding methyltriethoxysilane, and introducing it into the aerogel network by chemical grafting; S3: The sol is allowed to stand and gelled under the condition of gradient temperature increase, the gelling rate is controlled, the gel is placed in an autoclave, supercritical carbon dioxide is introduced, the temperature and pressure are precisely controlled, the solvent is rapidly discharged from the gel under the supercritical state, and after drying, a modified aerogel block is obtained; S4: Dispersing nanocellulose powder in water, adding a dispersant, and homogenizing the dispersion using a high-pressure homogenizer to obtain a finer fiber size and a more uniform dispersion effect, dissolving the bio-based polymer in an appropriate solvent, and mixing it evenly with the nanocellulose dispersion, using a vacuum-assisted impregnation method to evenly impregnate the mixed dispersion of nanocellulose and bio-based polymer into the aerogel block, and removing excess liquid by vacuum filtration to achieve a close composite of nanocellulose, bio-based polymer and aerogel matrix; S5: Prepare the photonic crystal film by self-assembly method, mix the reflective pigment with the solvent to form a uniform pigment slurry, add glass beads and infrared reflective agent to the pigment slurry and mix them evenly, mix the pigment slurry with the photonic crystal film, add surfactant to improve the dispersion and stability of the pigment, and apply the coating on the surface of the composite thermal insulation material by combining spraying and scraping; S6: Curing the coating to firmly adhere the nanocellulose, photonic crystals, reflective pigments, glass beads, infrared reflective agents, and bio-based polymers to the surface of the material.
7. The method for preparing a building thermal insulation material based on modified aerogel according to claim 6, characterized in that: In the S4, the nanocellulose powder is dispersed in water to form a dispersion with a concentration of 5 to 10%, a dispersant is added, and its addition amount is controlled to be 1 to 3% of the mass of the nanocellulose, and the dispersion is homogenized by a high-pressure homogenizer, the pressure is controlled at 20 to 40 MPa, and the treatment time is 30 to 50 minutes, the bio-based polymer is dissolved in water, and its concentration is controlled to be 5 to 15%, and the bio-based polymer is evenly mixed with the nanocellulose dispersion, and the mixed dispersion of nanocellulose and bio-based polymer is evenly impregnated into the aerogel block by a vacuum-assisted impregnation method, the vacuum degree is controlled at -0.08 to -0.1 MPa, and the impregnation time is 2 to 4 hours, and the excess liquid is removed by vacuum filtration to achieve a close composite of the nanocellulose, bio-based polymer and aerogel matrix.
8. The method for preparing a building thermal insulation material based on modified aerogel according to claim 6, characterized in that: In S5, a photonic crystal film is prepared by a self-assembly method, and the film thickness is controlled to be 50 to 200 nm. A reflective pigment is mixed with a solvent to form a uniform pigment slurry with a pigment concentration of 10 to 30%. Glass beads and infrared reflectors are added to the pigment slurry, and the addition amount is controlled to be 5 to 15% of the pigment mass, and the mixture is mixed evenly. The pigment slurry is mixed with the photonic crystal film, and sodium dodecyl sulfate is added, and the addition amount is controlled to be 1 to 5% of the pigment mass to improve the dispersibility and stability of the pigment. A coating is applied on the surface of the composite thermal insulation material by a combination of spraying and scraping, and the coating thickness is controlled to be 10 to 50 μm.
9. The method for preparing a building thermal insulation material based on modified aerogel according to claim 6, characterized in that: The modified aerogel is a modified aerogel with a three-dimensional network structure formed by copolymerization of methyltriethoxysilane and ethyl orthosilicate. The modified aerogel has a multi-level pore structure, wherein the pore structure includes micropores, mesopores and macropores, and glass microbeads are dispersed in the modified aerogel.
Citation Information
Patent Citations
Preparation method of heat-insulating TiO2 / SiO2 composite aerogel material
CN109603696A
Nano-porous thermal insulation material
CN111574210A
Carbon nanotube aerogel-based composite shaped phase change material and preparation and application thereof
CN114106779A
Water-based thermal insulation coating prepared from hydrophobic silicon dioxide aerogel and preparation method of water-based thermal insulation coating
CN117126571A
Radiation heat regulation and control thermal protection structure and thermal protection system of high-speed aircraft
CN117622462A
Cited By
Polyurethane composite aerogel sheet as well as preparation method and application thereof
CN120818229A
Lightweight thermal-insulation cement-based composite material and preparation method thereof
CN121318331A
